Large-Scale Dryland Cropping Systems - A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2015)
A large-scale dryland cropping systems research and demonstration project at the Southwest Research-Extension Center near Tribune, Kansas, evaluated two summer crops (corn and grain sorghum) along with winter wheat in crop rotations varying in length from 1 to 4 years. The rotations were continuous grain sorghum, wheat-fallow, wheat-corn-fallow, wheat-sorghum-fallow, wheat-corn-sorghum-fallow, and wheatsorghum- corn-fallow. The objective of the study is to identify cropping systems that enhance and stabilize production in rain-fed locations to optimize economic crop production. Averaged across the past 7 years, wheat yields ranged from 22 to 25 bu/a and were not affected by length of rotation. Corn and grain sorghum yields (7-year average) were about twice as great when following wheat than when following corn or grain sorghum. Grain sorghum yields were almost twice as great as those of corn in similar rotations.
Keywords: cropping systems; tillage systems; soil fertility; irrigation; fallow replacement; forage rotations; corn; wheat; sorghum; no-till